Implementation of Green Practice In Improving Service Quality At The Front Office Department At Mercure Bali Legian - Ni Kadek Helen Kusuma Dewi; Nyoman Mastiani Nadra; I Ketut Suarja; Ni Nyoman Triyuni; I Ketut Astawa (The Postgraduate School of Tourism Sahid Polytechnic, 2023)
Purpose: This study aims to determine the application of green practice in improving the service quality of the front office department at Mercure Bali Legian. Research methods: The data collection method was an observation, interviews, distributing questionnaires, and a literature study. The sampling technique was accidental sampling, with a total sample of 68 respondents and three informants. They collected data using online questionnaires distributed to respondents. Results and discussion: The application of green practice in improving the service quality of the front office department at Mercure Bali Legian has been maximally implemented, starting from the application of green action, green food, and green donation. Implication: The application of this green practice has a positive impact on improving the quality of service in the front office department, especially in helping work become more efficient and practical without using too many manual systems. Keywords: Implementation, green practice, service quality, front office department, hotel.